Diplectanidae (Monogenea) parasites of fish of the Kerkennah Islands (Tunisia) - Euzet, L. (Archives de l'Institut Pasteur de Tunis, 1984)
Eleven Diplectanidae (Monogenea) gill parasites from various Sparidae and Serranidae of the Kerkennah Islands are noted. Three new species: Lamellodiscus hilii, L. bidens, L. impervius, parasites of Puntazzo puntazzo (Sparidae) are described.